Evaluasi Faktor Penyebab Downtime Dengan Pendekatan OEE dan FMEA Pada Proses Produksi Mesin MGTR-RF15 - Meirani Id’ha Khusainiah; Indah Apriliana Sari Wulandari (Physical Sciences, Life Science and Engineering, 2024)
This research evaluates the efficiency of the MGTR-RF15 machine at RMP that focuses on raffia packing. In the last 6 months, MGTR-RF15 has experienced 100 times downtime which has caused the production process to stop temporarily, hampering the fulfillment of customer requests and increasing logistics costs. This study aims to determine the level of machine efficiency, determine the cause of the highest risk, and provide alternative suggestions for improvement. This research uses the Overall Equipment Effectiveness (OEE) and Failure Mode and Effect Analysis (FMEA) approaches. MGTR-1F15 OEE value of 82.91% is below international standards with availability as the dominant factor affecting efficiency. The FMEA identified the bent strap clamp iron as the critical failure with the highest risk worth RPN 280. Root Cause Analysis (RCA) shows the root cause of the downtime problem so that alternative recommended improvements include routine training, implementation SOPs, inspection raw materials, and selecting high-quality suppliers.